The Effect of Pollen on The Cross of Black Corn, Waxy Corn (Zea Mays Ceratina), and Sweet Corn (Zea Mays Saccharata) on the Seed Characters - Erny Ishartati (Gontor AGROTECH Science Journal, 2020)
The expression of genes resulting from crosses from male parents and female parents will be seen in the next plant generation, where the pollen effect of male parent called xenia effect really determines the direction of its expressiveness to produce superior cultivars. Therefore, this study aims to determine the effect of xenia on qualitative and quantitative characters as well as to obtain information on prospective male lines as parents used to form hybrid cultivars. The research was conducted at the Experimental Farm of University of Muhammadiyah Malang, East Java. The method used was a single plant selection. The cross treatments used were selfing and crossing. Observations were made on qualitative and quantitative characters. Qualitative character data were analyzed using a descriptive statistical scoring approach. Quantitative data were analyzed using independent t test with a level of 5%. The results showed that the pollen  affected the variable seed color, seed shape, ear weight, ear length, ear diameter, number of seed rows, weight of 100 seeds, seed length and seed width of several crosses. From this research, it was obtained several prospective lines that can be used as male parents for the formation of hybrid corn cultivars having different seed characters.